Modeling and Analysis of the Impact of Media Based Awareness Efforts on Asthma Development in a Polluted Environment - Verma, Vinay; Verma, Sandhya Rani; Pathak, Rachana; Vimlesh, (Discontinuity, Nonlinearity, and Complexity, 2026)
There have sometimes been reports of an influence of behavioral reactions and awareness campaigns on epidemic breakouts. From a public health perspective, knowledge and behavioral changes are crucial, but it is unclear how much they affect the course of the pandemic. Using a mathematical model, we explore the impact of media awareness efforts on the onset of asthma in a population that is genetically susceptible to pollution. Assessments are made of the system's durability and the prerequisites for the existence of the unique positive stable state. Lyapunov's function analysis identifies the unique positive steady state as being both locally and globally asymptotically stable. Campaigns to raise awareness can help prevent the expansion of the asthma pandemic, but immigration maintains the condition endemic, according to the model research. The model is also numerically analyzed to confirm the analytical results and ascertain how many important parameters affect the asthma outbreak.